Detection of the extended spectrum β-lactamase produced by Escherichia coli from dairy cows by using the Vitek-2 method in Tulungagung regency, Indonesia - Effendi, Mustafa Hilmi; Tyasningsih, Wiuwki; Suwarno, Suwarno; Koesdarto, S.; Estoepangestie, A. T. Soelih; Putra, Akyun Ruzaqi (Iraqi journal of veterinary sciences, 2020)
The use of antibiotics in inappropriate on food producing animals can lead to resistance many of the pathogenic bacteria to the various types of antibiotics, one of which is the Escherichia coli (E. coli) which produces extended spectrum β-lactamase (ESBL). Antibiotic resistance in animals and humans has become a global problem that needs attention and immediate management by using specific antibiotics that used for therapeutic the infected animals. The aim of this study was to isolate and detect E. coli producing ESBL. All E. coli from the surface of dairy cow rectal swabs in Sendang District, Tulungagung Regency, Indonesia using the Vitek-2 method. The number of rectal swab samples used in the present study was 50. The results of this study showed that all the samples were suspected of being E. coli, based on the morphological growth of colonies on the EMBA media. The isolates were identified by using the biochemical tests. All the samples were positive. In this study the double disc synergy test (DDST) method was using to confirm the ESBL. The antibiotics were used amoxicylyn-clavulanate, ceftazidime and cefotaxime for DDST. In additional ESBL confirmation test was used the Vitek-2 method. The presence of ESBL producing by E. coli isolated from rectal dairy swabs in tulungagung was 6% (3/50)